Transcriptome analysis reveals effects of ethynylestradiol and bisphenol A on multiple endocrine and metabolic pathways in the pituitary and liver of female Atlantic cod (Gadus morhua) - Yadetie, Fekadu; Zhang, Xiaokang; Reboa, Anna; Noally, Gwenaëlle Samantha Chloe; Eilertsen, Mariann; Fleming, Mitchell Stewart; Helvik, Jon Vidar; Jonassen, Inge; Goksøyr, Anders; Karlsen, Odd André (Frontiers in Endocrinology, 2025)
IntroductionThe pituitary and liver are among the main sites of action of estrogens in fish. Years of research has shown that xenoestrogens can interfere with functions of estrogens. There is however incomplete understanding of xenoestrogen targets genes, their molecular mechanisms and potential effects in some of the target organs, particularly the pituitary.MethodsWe performed a comprehensive analysis of pituitary and liver transcriptome 72 h after injection of ethynylestradiol (EE2: 10, 50 or 250 nmol/kg body weight/bw) and bisphenol A (BPA: 8, 40 or 200 μmol/kg bw) in juvenile female Atlantic cod (Gadus morhua).ResultsA broad range of reproductive and metabolic pathways were affected in both organs by BPA and EE2. In the pituitary, effects on the expression of many genes associated with reproduction-related hormonal pathways including the gonadotropin system, as well as genes in processes such as cell differentiation and metabolic homeostasis were observed. In the liver, in addition to upregulation of well-known estrogen marker genes, effects on metabolic pathways, in particular, a coordinated downregulation of genes in the triglyceride synthesis pathways were observed.DiscussionThe results suggest that estrogenic compounds affect a broad range of reproductive and metabolic processes in the pituitary. The alterations in the liver unravel the transcriptional changes underlying metabolic remodeling during estrogen induced vitellogenesis. This study provides new insights into mechanisms of endocrine and metabolic interactions that can be potential targets of environmental estrogens in fish. The study also identifies potential gene expression biomarkers for pituitary and liver effects of xenoestrogens.